The evidence of compelling arguments in agenda building: Relationships among public information subsidies, media coverage, and risk perceptions during a pandemic outbreak. Issue 1 (28th January 2014) - Rim, Hyejoon; Hong Ha, Jin; Kiousis, Spiro
Abstract : Purpose: – This paper aims to explore the links among health authorities' public relations efforts, news media coverage, and public perceptions of risk during the H1N1 pandemic outbreak. Design/methodology/approach: – This study used a triangulation of research methods by comparing public relations materials, media coverage, and public opinion. The data were collected from a federal government web site, national newspapers, and national polls. Findings: – The data revealed a positive relationship between information subsidy attention and media attention to the H1N1 disease as well as the severity attribute. The salience of the severity attribute in information subsidies was linked with increased H1N1 salience in media coverage, extending the testing of the compelling-arguments hypothesis to an agenda-building context. However, there was no association between salience of the severity attribute and public risk perceptions. Research limitations/implications: – The study provides evidence for public relations effectiveness. However, the limited influence of the severity frame on the public's risk perception suggests a gap between news coverage and the public's view. Framing that effectively empowers the public to engage in desired behavior should be further studied for the success of a public health campaign. The study is limited to examining the severity attribute. A future study should pay more attention to different issue attributes or other frames. The media sample was limited to newspapers and thus lacks generalizability. Originality/value: – The study contributes to public relations scholarship by demonstrating how information subsidies influence media agendas and public opinion in a health communication context. The public health authorities' role in influencing media agenda should be stressed.